The Effect of Vehicle Body Shapes on the Near Wake Region and Drag Coefficient: A Numerical Study (Journal of Engineering, 2016)
The purpose of this paper is to gain a good understanding about wake region behind the car body due to the aerodynamic effect when the air flows over the road vehicle during its movement. The main goal of this study is to discuss the effect of the geometry on the wake region and the aerodynamic drag coefficient. Results will be achieved by using two different shapes, which are the fastback and the notchback. The study will be implemented by the Computational Fluid Dynamic (CFD) by using STAR-CCM+® software for the simulation. This study investigates the steady turbulent flow using k-epsilon turbulence model. The results obtained from the simulation show that the region of the air separation behind the vehicle varies with the variation of the body design. The minimum drag coefficient can be achieved with notch-back since the separation of the air is less as compared with fastback end. These results are demonstrated by pressure distribution and velocity distribution which offer a good understanding of the flow behavior around the vehicle bodies.